THE USE OF DIAGONAL SIMILARITY LAWS IN THE COMPARATIVE STUDY OF THE PROPERTIES OF CHEMICAL ELEMENTS - Kuchkarov Mexriddin Asamovich; Malikova Muxlisa (Web of Journals Publishing, 2023)
This article examines the role of comparative study, analysis of the properties of chemical elements in the teaching of chemistry. He focuses on analyzing the diagonal similarity of the elements. This approach is based on the promotion of scientific literacy of students.
Keywords: diagonal similarity, horizontal similarity, vertical similarity, comparative analysis, competence in the field of scientific awareness, predictive approach, creative thinking, creative thinking, Poling scale.